PENGARUH MODEL PEMBELAJARAN SUPERITEM BERDASARKAN PROSEDUR NEWMAN TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIS SISWA MTSN 3 CILEGON - Titin Mastinah; Hamidah Hamidah; Vidya Ayuningtyas (Jurnal Lebesgue : Jurnal Ilmiah Pendidikan Matematika, Matematika dan Statistika, 2023)
This study aims to find out: 1) The significant influence of the Superitem learning model on the mathematical problem solving ability of MTSN 3 Cilegon students; 2) How is the mathematical problem solving ability of students given the Superitem learning model based on the Newman procedure. The population in this study is all grade VIII students in MTsN 3 Cilegon for the 2021/2022 academic year in the even semester consisting of 6 classes. The sample was randomly selected, namely class VIII B as the experimental class and VIII D as the control class. The hypothesis test used is the T Test to determine the average difference and the correlation test to determine the effect of variable x with variable y. The results of the hypothesis show that 1) There is a significant influence of the Superitem learning model on students' mathematical problem solving ability by 62% and 38% others are influenced by other factors; 2) Students' mathematical problem-solving skills based on Newman's procedure, there are still many students who do not do the stages of writing answers or re-checking answers. In addition, students often find it difficult when transforming problems and solving problems